2018
DOI: 10.3390/ma11081335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strain Heterogeneities on Microstructure, Texture, Hardness, and H-Activation of High-Pressure Torsion Mg Consolidated from Different Powders

Abstract: Severe plastic deformation techniques, such as high-pressure torsion (HPT), have been increasingly applied on powder materials to consolidate bulk nanostructured materials. In this context, the aim of the present study is to compare the plastic deformation characteristics during HPT of two distinct Mg-based powder precursors: (i) atomized micro-sized powder and (ii) condensed and passivated nanopowder. Dynamic recrystallization could take place during HPT consolidation of the atomized powder particles while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…As shown on the STEM Bright Field (BF) image (Fig. 1), the material processed by severe plastic deformation exhibits a submicron grain size, in agreement with an earlier study [22,23]. The grain size is slightly finer than in bulk Mg processed by SPD [X2] due to a small fraction of nanoscaled oxide particles pinning boundaries.…”
Section: Methodssupporting
confidence: 87%
“…As shown on the STEM Bright Field (BF) image (Fig. 1), the material processed by severe plastic deformation exhibits a submicron grain size, in agreement with an earlier study [22,23]. The grain size is slightly finer than in bulk Mg processed by SPD [X2] due to a small fraction of nanoscaled oxide particles pinning boundaries.…”
Section: Methodssupporting
confidence: 87%
“…[7] A breakdown in Hall-Petch behavior and inverse Hall-Petch relationship, or grain refinement softening, has been reported in pure Mg in bulk samples with grain sizes smaller than a few micrometers [8][9][10] although grain refinement hardening, at much smaller grain sizes, has been reported in samples of pure magnesium consolidated from powders. [11,12] Room-temperature annealing has been reported in pure Mg processed by high-pressure torsion (HPT), leading to an increase in strength, [13] which also supports the occurrence of grain refinement softening in this material. The grain refinement softening is usually associated with a remarkable increase in strain rate sensitivity and exceptional increase in formability in pure magnesium.…”
Section: Introductionmentioning
confidence: 90%
“…In another investigation, Panda et al 12) reported a more detailed study concerning the microstructural development during HPT using two different initial powders (atomized and condensed) and observed substantial differences in the development of the microstructure, texture, local strain heterogeneities, and hardness in the two types of products. Such differences resulted in a significant effect on the hydrogen activation kinetics to form hydrides.…”
Section: Processing Of Mg and Mgh 2 Powders By Spd Techniquesmentioning
confidence: 99%